Tensões e negociação na convivialidade multicultural em Brick Lane (2003), de Monica Ali - Nagib, Francieli Aparecida Muniz (2011)
The diasporic experience of Bangladeshi immigrants in England and the multicultural conviviality between white British society and the Bangladeshi diasporic community within the context of British Black Literature is analyzed in Monica Ali's Brick Lane (2003). The novel portraits Bangladeshi diasporic people living in the United Kingdom, supposed to have "motherly" attitudes towards ex-colonials. However, in a multicultural milieu they face a struggle between their tradition and a liberation trend in the British capital from the rules ethnically imposed upon. The dissertation's principal aim is an analysis of the social relationships and the interaction processes between the Bangladeshi diasporic people and the hegemonic British society, with special emphasis on the conflicts between different cultures, the type of treatment given to Bangladeshi diasporic people in London, negotiations within a hegemonic context and the coexistence politics of multiculturalism. Contemporary diaspora, multiculturalism as a political strategy and globalizing Diasporas are investigated from the principles of postcolonial theory. The theories on which the discussion on diaspora are based come from Hall, Brah, Ashcroft and Cohen; with regard to multiculturalism, theories hail from the works by Hall, Semprini, Gilroy, Wieviorka and others. Results show that multicultural conviviality may lead certain diasporic people to live apart from and hermetically closed to the hegemonic society, or rather, they fail in their attempt to interact with the adopted country, especially since this context is permeated with racism and discrimination directed to the immigrants. Contrastingly when the hegemonic context reveals attitudes of multicultural communities building, in which racial prejudice and exclusion are minimized, conviviality and integration may be consolidated.